O-157 Female body mass index (BMI) influences pregnancy outcomes: An evaluation of 4349 IVF/ICSI cycles. (30th June 2022) - Nicoletti, A; Petersen, C.G; Massaro, F.C; Petersen, B; Vagnini, L; Ricci, J; Zamara, C; Oliani, A.H; Oliveira, J.B.A; Dieamant, F; Franco, J.G.
Abstract: Study question: Does female body mass index (BMI) impair pregnancy outcomes after IVF/ICSI cycles? Summary answer: High BMI (overweight and obesity) and low BMI (underweight) are associated with decreased clinical pregnancy and live birth rates and an increased miscarriage rate. What is known already: Obese women undergoing treatment for infertility may face problems, such as the need for higher doses of drugs to stimulate ovulation, oocyte morphological changes, reduction in fertilization and implantation rates, and embryo quality. Compared to women of normal BMI, obese women submitted to IVF may present reduced rates of clinical pregnancy and live births and an increased miscarriage rate. Regarding the effects of low BMI, unfavourable pregnancy outcomes and infertility problems have been described, but evidence is still scarce and conflicting. Study design, size, duration: A prospective analysis was performed of 4349 couples who underwent IVF/ICSI treatment and fresh embryo transfer. Only one cycle per couple was considered. Exclusion criteria included abnormal karyotype, uterine defects, evidence of hydrosalpinx, infections, endocrine problems, coagulation defects or thrombophilia and autoimmune defects. Couples were stratified into four groups by female BMI: <18.5kg/m 2 (underweight); 18.5-24.9kg/m 2 (normal weight); 25-29.9kg/m 2 (overweight); and ≥30kg/m 2 (obesity). Clinical pregnancy, miscarriage and live birth rates were the outcomes analysed. Participants/materials, setting, methods: Variables such as age, duration/type of infertility, previous embryo transfers, aetiologies, endometrial thickness, type of ovarian stimulation, and number/quality/development stage of embryo transferred were included as potential confounding factors. For group comparisons, the t test or chi-square test was used. Multivariate logistic regression analyses were performed to evaluate the associations between BMI and the probabilities of clinical pregnancy (CP), miscarriage and live birth (LB). Normal-weight patients were considered as the reference group. Main results and the role of chance: Regarding confounding factors, no significant differences between BMI groups were observed. -BMI-group comparisons showed that CP, miscarriage and LB rates significantly worsened with the increase in BMI (overweight and obesity groups). Miscarriage and LB rates also worsened with the decrease in BMI (underweight group) (Table 1 ). -Compared with the normal-weight group, the overweight and obesity groups had significantly reduced rates of CP (19%/29%, respectively) and LB (27%/40%, respectively) and an increased rate of miscarriage (1.7x and 2.3x, respectively). Underweight was associated with a 49%-reduced rate of LB and a 3.0x increase in the rate of miscarriage (Table 2 ). Limitations, reasons for caution: Differences in sample size between BMI groups may have influenced the results. In clinical outcomes, only fresh transfers were considered (not cumulative data). Population characteristics should be considered when interpreting the results. Wider implications of the findings: The study suggests that higher BMI (overweight and obesity) and lower BMI (underweight) in women have a detrimental effect on ART outcomes, especially regarding the evolution of pregnancies. Problems associated with abnormal BMI should be discussed when advising couples interested in fertility treatment. Trial registration number: Not applicable.